2013
DOI: 10.1002/term.1741
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell bioengineering strategies to widen the therapeutic applications of haematopoietic stem/progenitor cells from umbilical cord blood

Abstract: Umbilical cord blood (UCB) transplantation has observed a significant increase in recent years, due to the unique features of UCB haematopoietic stem/progenitor cells (HSCs) for the treatment of blood-related disorders. However, the low cell numbers available per UCB unit significantly impairs the widespread use of this source for transplantation of adult patients, resulting in graft failure, delayed engraftment and delayed immune reconstitution. In order to overcome this issue, distinct approaches are now bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 191 publications
(198 reference statements)
0
17
0
Order By: Relevance
“…Cord blood haematopoietic stem and progenitor cells (cbHSPCs) have attracted considerable interest as a full value alternative to bone marrow HSPCs. The number of cbHSPC transplants is increasing from year to year, but their low number in one cord blood sample is a significant limitation to expanded application of these cells [ 1 ]. In this connection, the development of ex vivo approaches for cbHSPC amplification and differentiation into certain haematopoietic lineages is a primary goal of cell technologies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cord blood haematopoietic stem and progenitor cells (cbHSPCs) have attracted considerable interest as a full value alternative to bone marrow HSPCs. The number of cbHSPC transplants is increasing from year to year, but their low number in one cord blood sample is a significant limitation to expanded application of these cells [ 1 ]. In this connection, the development of ex vivo approaches for cbHSPC amplification and differentiation into certain haematopoietic lineages is a primary goal of cell technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, most of such experiments were conducted on stromal and haematopoietic cells isolated from bone marrow [ 1 ]. The results of these studies demonstrated that MSCs, applied as a feeder layer, may considerably influence the co-cultured HSCs, in particular, changing the ratio of poorly differentiated and committed progenitors [ 3 , 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest the existence of inhibitory effects of FBS addition to the culture medium on the megakaryopoiesis ex vivo and provide insights on how a BM-MSC feeder layer, used as accessory cells, contribute either through direct cell-cell contact and/ or soluble factor signaling to modulate proliferation, maturation and development of Mks as well as platelet production from the expanded UCB progenitors. The protocol developed benefits from the use of UCB progenitors because these are readily available from simple collection procedures, having less risk of provoking graft-versus-host disease and a high proliferative rate in vitro compared with adult counterparts [35]. This study provides evidence that UCB CD34 þ -enriched cells differentiated in the presence of a BM-MSC feeder layer are able to generate polyploid Mks (DNA content >4N) and finally to produce functional platelets through the use of a serum-free system supplemented by cytokines (TPO and IL-3).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, in our culture conditions, the differentiation potential of UCB CD34 þ cells, expanded by use of the Z9 cocktail, was shifted toward myeloid lineage, as previously reported [19], with significantly higher megakaryocytic content, considerably affecting the differentiation stage. Indeed, expanded cells in the Z9 condition Although FBS has been widely used as a culture medium supplement to support the growth and proliferation of several animal cells, the development of serum-free/animal originefree culture systems is crucial to meet the requirements of the regulatory agencies [34], improving the batch-to-batch consistency and safety of cellular products [35]. In this study, QBSF-60 was assessed as a medium for differentiation stage, supplemented by Cyt and/or Feeder conditions, resulting in a significantly higher EY, %CD41 and %CD42b and higher polyploid content (>4N, %) when compared with a nondefined medium containing FBS (IMDMþ10% FBS).…”
Section: Discussionmentioning
confidence: 99%